2018
DOI: 10.1136/vr.104891
|View full text |Cite
|
Sign up to set email alerts
|

Signalment risk factors for cutaneous and renal glomerular vasculopathy (Alabama rot) in dogs in the UK

Abstract: 20Seasonal outbreaks of cutaneous and renal glomerular vasculopathy (CRGV) have been reported 21 annually in UK dogs since 2012 yet aetiology of the disease remains unknown. The objectives of this 22 study were to explore whether any breeds had an increased or decreased risk of being diagnosed with 23 CRGV, and to report on age and sex distributions of CRGV cases occurring in the UK. Multivariable

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 9 publications
2
23
0
Order By: Relevance
“…After accounting for other variables, 23 breeds with more than 4 cases showed elevated odds of osteosarcoma compared to crossbreeds and, of these breeds, the Rottweiler, Rhodesian Ridgeback and Great Dane had over ten times the odds. Although the Rottweiler and Great Dane have been reported as at-risk breeds previously, the current study is the rst to identify predisposition for the Rhodesian Ridgeback [2,4,5,9,11,12,24]. Rhodesian Ridgebacks could have been omitted from previous work owing to selection bias, which refers to a scenario in which the composition of the study group differs from the source population, and this biases the association between exposure and outcome [33,34].…”
Section: Breed Variablementioning
confidence: 99%
See 1 more Smart Citation
“…After accounting for other variables, 23 breeds with more than 4 cases showed elevated odds of osteosarcoma compared to crossbreeds and, of these breeds, the Rottweiler, Rhodesian Ridgeback and Great Dane had over ten times the odds. Although the Rottweiler and Great Dane have been reported as at-risk breeds previously, the current study is the rst to identify predisposition for the Rhodesian Ridgeback [2,4,5,9,11,12,24]. Rhodesian Ridgebacks could have been omitted from previous work owing to selection bias, which refers to a scenario in which the composition of the study group differs from the source population, and this biases the association between exposure and outcome [33,34].…”
Section: Breed Variablementioning
confidence: 99%
“…Furthermore, it was hypothesised that purebred dogs in general have higher odds of osteosarcoma than crossbreeds. Since reportedly predisposed breeds possess large body mass, a related hypothesis was that heavier weight categories have higher odds of osteosarcoma [2,5,9,12,24]. Secondary to the breed and body mass hypotheses, we also proposed that dogs with conditions which become inherited during breeding for short leg length, such as chondrodystrophy, would be protected from osteosarcoma compared with non-chondrodystrophic breeds [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Also priortised at the 3rd IDHW was movement towards open access publication to encourage wider disemination of research findings and there is some evidence that research papers are increasingly likely to be published as open access since then [37,53,54]. There has also been evidence of increased research output on two key areas identified as priorities at the 3rd IDHW 2017: disease prevalence/incidence, risk factors, and geographic spread [53,[55][56][57][58] and also quality-of-life and end-of-life data [59,60].…”
Section: Ipfd Harmonization Of Genetic Testing For Dogs: An Internatimentioning
confidence: 99%
“…The aetiology is unknown although multiple possibilities have been proposed, including ingestion of bacteria-associated shiga toxin [1, 2, 4, 5, 7, 8, 10] However, studies have failed to consistently identify the presence of shiga toxin, or bacteria or viruses within tissues from affected cases [1, 4, 5]. Electron microscopy with immunostaining has also failed to identify immune-complex deposition in affected cases [4, 5, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Electron microscopy with immunostaining has also failed to identify immune-complex deposition in affected cases [4, 5, 8]. Despite this, several risk factors for development of the condition have been identified, including being from the hound or gundog Kennel Club groups, and certain individual breeds such as English springer spaniel, flat-coated retriever, Hungarian vizsla and whippet, and being female and neutered [10]. The majority of diagnoses are made between November and May, and case distribution is strongly linked to woodland habitats [11].…”
Section: Introductionmentioning
confidence: 99%